KARAKTERISTIK IKAN KERAPU DI PASAR ARUMBAI AMBON - Ruslan H. S. Tawari; Friesland Tuapetel; Kedswin G. Hehanussa; Julian Tuhumury; Selfi Sangadji; Kasmin Kasmin (Universitas Pattimura, 2024)
Arumbai Market in Ambon City, Maluku Province, is a central hub for the trade of fishery products, particularly groupers. This study aims to describe the origin of grouper catches and to identify the species and sizes of groupers marketed at Arumbai Market. Groupers, which belong to the family Serranidae, are the primary predators in coral reef ecosystems. Fish identification was conducted based on Allen's guide and verified through FishBase. The study was conducted from December 2022 to February 2023 using a survey method through direct observation and interviews. Data were analyzed descriptively and presented in tables and graphs. The results showed that groupers at Arumbai Market come from four main locations: Manipa (34.47%), Liang (26.81%), Latuhalat (24.26%), and Pulau Tiga (14.47%). Eight dominant species of groupers in this market are Variola albimarginata (44.64%), Cephalopholis miniata (20.60%), Epinephelus fasciatus (12.45%), Epinephelus ongus (6.44%), Cephalopholis urodeta (6.44%), Cephalopholis sonnerati (5.58%), Epinephelus areolatus (3.00%), and Epinephelus fuscoguttatus (0.86%). Grouper sizes vary, with Cephalopholis miniata having a maximum size of 27.1 cm and a minimum size of 19.9 cm. This study provides essential information on the origin of catches, species dominance, and sizes of groupers marketed, which can serve as a basis for better fishery management. These findings indicate a significant potential for grouper trade in the region and highlight the importance of sustainable management to preserve the continuity of coral reef ecosystems and grouper populations.